Effect of total solids content on biohydrogen production and lactic acid accumulation during dark fermentation of organic waste biomass. (January 2018) - Ghimire, Anish; Trably, Eric; Frunzo, Luigi; Pirozzi, Francesco; Lens, Piet N.L.; Esposito, Giovanni; Cazier, Elisabeth A.; Escudié, Renaud
Highlights: H2 and by-products production were investigated in solid state DF of food waste. Effects of TS content and H2 partial pressure on substrate conversion were studied. 15% TS was found to be limiting for H2 production during solid state DF. Abstract: Production of biohydrogen and related metabolic by-products was investigated in Solid State Dark Fermentation (SSDF) of food waste (FW) and wheat straw (WS). The effect of the total solids (TS) content and H2 partial pressure (ppH2 ), two of the main operating factors of SSDF, were investigated. Batch tests with FW at 10, 15, 20, 25 and 30% TS showed considerable effects of the TS on metabolites distribution. H2 production was strongly inhibited for TS contents higher than 15% with a concomitant accumulation of lactic acid and a decrease in substrate conversion. Varying the ppH2 had no significant effect on the conversion products and overall degradation of FW and WS, suggesting that ppH2 was not the main limiting factor in SSDF. This study showed that the conversion of complex substrates by SSDF depends on the substrate type and is limited by the TS content.